EMPOWERING MSMES IN GEDANGSARI, YOGYAKARTA: CANVA AS A KEY TOOL FOR DIGITAL PROMOTION - Hadi, Syamsul; Hidayat, Riskin; Susanti, Dyah Ari; Purnasari, Eni; Bin Pinjaman, Saizal (SMARTINDO, 2024)
The objective of this community service initiative is to enhance the local economy by promoting the use of the creative digital tool Canva among the community of Sengonkerep, Yogyakarta. This area is known for its handmade crafts, traditional foods, and agricultural products. The initiative aims to enable the community to market their products more effectively through digital platforms, thereby fostering sustainable development for micro, small, and medium enterprises (MSMEs). The methods employed include workshops and hands-on training on using Canva as a digital tool for online promotion, as well as education to improve understanding of digital marketing strategies. Results from this activity indicate that 80% of participants have grasped how to use Canva for product promotion. Furthermore, participants expressed confidence that branding with Canva can enhance product image and increase consumer traffic. However, the success and sustainability of this initiative require effective collaboration with various stakeholders, including academic institutions, government entities, and other business actors. Therefore, this service activity recommends closer cooperation among all relevant parties to support sustainable local economic growth.